Effect of Different Colored LED Lighting on the Growth and Pigment Content of Isochrysis zhanjiangensis under Laboratory Conditions - Bu Lv; Ziling Liu; Yu Chen; Shuaiqin Lan; Jing Mao; Zhifeng Gu; Aimin Wang; Feng Yu; Xing Zheng; Hebert Ely Vasquez (Journal of Marine Science and Engineering, 2022)
Light is one of the most important environmental factors affecting the growth and reproduction of algae. In this study, the effect of various LED colors on the productivity, chlorophyll (Chl-a, Chl-b, and total Chl), protein, and carbohydrate content of Isochrysis zhanjiangensis in indoor culture was investigated. Microalgae monocultures were cultivated under five different colors (red, green, blue, yellow, and white) for twenty-one days. The microalgae cultured under red light exhibited a higher specific growth rate (0.4431 ± 0.0055 µ day−1), and under white light a higher productivity (0.0728 ± 0.0013 g L−1 day−1). The poorest performance was observed under yellow and green lights. Interestingly, green light exhibited the highest levels of chlorophylls (Chl-a, 1.473 ± 0.037 mg L−1; Chl-b, 1.504 ± 0.001 mg L−1; total Chl, 2.827 ± 0.083 mg L−1). The highest protein content was observed under the white light (524.1935 ± 6.5846 mg L−1), whereas the carbohydrate content was remarkably high under the blue light (24.4697 ± 0.0206 mg L−1). This study is important in terms of the selection of light at the appropriate color (wavelength) to increase the content of organic compounds desired to be obtained indoors with the potential for commercially produced cultures.